Fucoxanthin identification and purification of brown algae commonly found in Lombok Island, Indonesia - yeni sulistiyani; AGUS SABDONO; NORMA AFIATI; HAERUDDIN HAERUDDIN (Society for Indonesian Biodiversity, 2021)
Abstract. Sulistiyani Y, Sabdono A, Afiati N, Haeruddin. 2021. Fucoxanthin identification and purification of brown algae commonly found in Lombok Island, Indonesia. Biodiversitas 22: 1527-1534. Fucoxanthin is a significant carotenoid pigment found in brown algae. Fucoxanthin is the most human-exploited pigment in brown algae due to its health benefits such as antioxidant, anti-diabetic, anti-obesity, anti-cancer, and anti-inflammatory activities. Therefore, fucoxanthin has been mass-produced on an industrial scale as a food supplement. This work focused on identifying, purifying and comparing the fucoxanthin yield diversity at one study site quantitatively. Three brown algae commonly found in Lombok waters have been studied in this work: Sargassum cf. granuliferum, Sargassum polycystum, and Sirophysalis trinodis. Fucoxanthin was successfully identified using HPLC methods, TLC and Spectra absorption analysis. Using HPLC, fucoxanthin was identified at 450 nm wavelength, with a retention time of 3.088-3.095 min. Based on the TLC result, the Rf value of fucoxanthin is 0.46-0.47, while the spectra absorption maxima are 447.6-448.4 nm. The highest fucoxanthin yield was found in S. polycystum, followed by S. cf. granuliferum and Sirophysalis trinodis with 3.01 ± 0.01 mg/g, 2.21 ± 0.002 mg/g, and 0.95 ± 0.01 mg/g, respectively.